The experience of tobacco withdrawal symptoms among current smokers and ex-smokers in the general population: Findings from nationwide China Health Literacy Survey during 2018-19 - Cui, Zi-yang; Li, Ying-hua; Liu, Zhao; Li, Li; Nie, Xue-qiong; Zhou, Xin-mei; Cheng, An-qi; Li, Jin-xuan; Qin, Rui; Wei, Xiao-wen; Zhao, Liang; Ladmore, Daniella; et al. (Frontiers in Psychiatry, 2023)
Objective To clarify the extent to which smokers in the general population experience tobacco withdrawal symptoms and whether such experience differs in those who continue to smoke and those who stopped smoking. Methods We included relevant questions in the nationally-representative China Health Literacy Survey (CHLS) conducted in 2018–2019. Among 87,028 participants, there were 22,115 ever-smokers aged 20–69 years who provided information on their smoking history and their experience of tobacco withdrawal symptoms. Multivariate logistic regressions were conducted to explore the association between withdrawal symptoms and other variables. Results Among ever-smokers, there were 19,643 (88.8%) current smokers and 2,472 (11.2%) ex-smokers. Among current smokers, 61.3% reported having tried to quit smoking in the past. Overall, 61.1% of current smokers reported experiencing withdrawal symptoms: 69.9% of those who tried to quit smoking in the past and 47.5% of those who did not. A lower proportion of ex-smokers experienced withdrawal symptoms (46.3%) and the difference remained significant after controlling for demographic characteristics (OR = 1.76, 95% CI 1.62–1.93, P < 0.001). The most commonly reported withdrawal symptoms in both current smokers and ex-smokers were craving, restlessness and anxiety. In the multivariable-adjusted analyses, those who experienced withdrawal symptoms when they tried to quit smoking (OR: 2.05, 95% CI: 1.86–2.27) were less likely to successfully quit. Conclusions The clinical picture of the tobacco withdrawal syndrome is the same in current smokers and in ex-smokers, but ex-smokers are less likely to have experienced it. The experience of discomfort when unable to smoke is common and seems likely to be a major factor contributing to maintaining smoking behavior not just among individuals seeking help with quitting smoking, but among smokers generally.